Media marketing in television talk shows on Kurdish satellite channels: An analytical study of the program (avin zhnu zhyan) - محمد, سالم نصرالدين; حسن, كاروان محمد (Sulaimani Journal for Humanities, 2019)
This research scrutinizes the media marketing in television talk-shows in Kurdish channels, within 10 years of presentation and more than 1,000 episodes (Avin Zhn u Zhyan) has been selected as a sample of the study. The methodology of content analysis is applied to study the sample consists of 42 episodes for the period of Six months The research concluded several conclusions as follows: 1. Through the results of the study, the social field is more preferable than other fields. 2. The most awareness campaigns that have been marketed with the program is about coexistence and social integration between individuals, as well as health issues in addition to other fields such as nationalism, agricultural, education, traffic and environmental awareness. 3. Discussing the issues and problems considered the most used method of addressing the contents of the program. 4. Artist and public figures are the most of hosted personalities in the program followed by government officials. 5. Singers obtain the highest percentages among the celebrities and public figures to promote their latest records and discuss their career. 6. Household cleaning products received the highest percentage of ads products followed by cosmetics materials.